Preparation of ceramic microlectromechanical systems (MEMS) using a gelcasting consolidation technique - S. M. Olhero (2008)
The present work focuses the preparation and characterisation of suspensions withthree different powders, ferrite, PZT and alumina, for the fabrication of 3D-shapedceramic structures by gelcasting. The characterization of powders by particle size ispresented together with the preparation and characterization of the resultingsuspensions by rheological and zeta potential measurements. Using 1-wt% of DispexA-40 is possible to prepare concentrated PZT and ferrite suspensions to beconsolidated by gelcasting. The workability of gelcasting technique is demonstratedon a range of component geometries suitable for MEMS applications.